Symbols and Meanings in The Mandailing Traditional Wedding (Rituals and Cultural Attributes) in The Cultural Revitalisation of The Alpha Generation - Asri Yulianda; Anna Leli Harahap; Shopiah Anggraini Rambe; Saprida Saprida; Muhammad Fauzi Romadhon Marpaung (EXCELLENCE: Journal of English and English Education, 2026)
This study aims to describe the symbols and meanings found in the rituals and cultural attributes of the Mandailing traditional wedding ceremony, as well as their relevance to the revitalisation of Mandailing Batak culture among Generation Alpha. This study employs a qualitative descriptive method, utilising data collection techniques such as observation, interviews, and documentation conducted in the village of Hutagodang. The data were analysed using Roland Barthes’s semiotic theory, which encompasses denotative, connotative, and mythical meanings. The results of the study indicate that the rituals of makkobar, berinai, marhaban, and mangupa-upa, as well as the traditional clothing and food of the Mandailing, contain symbolic meanings such as respect, togetherness, responsibility, prayer, and hopes for married life. Semiotic analysis shows that each ritual and cultural attribute possesses denotative, connotative, and mythical meanings that reflect the cultural values of the Mandailing community. This study also indicates that Generation Alpha is still familiar with the practice of Mandailing traditional weddings, but does not yet fully understand the symbolic meanings contained within them. Therefore, cultural revitalisation efforts are required to ensure that Mandailing cultural values are preserved and passed on to the younger generation.